Dermatologic Surgical Care for Transgender Individuals. Issue 3 (March 2019) - Marks, Dustin H.; Awosika, Olabola; Rengifo-Pardo, Monica; Ehrlich, Alison
Abstract : BACKGROUND: Transgender individuals experience common and unique dermatologic concerns from severe acne associated with testosterone therapy in transmen to complications due to illicit silicone injections in transwomen. Currently, 2 survey studies and 4 reviews have addressed the dermatologic care of transgender individuals. However, none of them provide a focus on the dermatologic surgeon. OBJECTIVE: To assess the dermatologic considerations in transgender individuals and the role of dermatologic surgeon in their care. METHODS: The PubMed and MEDLINE databases were reviewed in June 2018 using keywords, such as transgender, procedures, hair removal, laser, and hormone therapy. RESULTS: In total, 48 relevant publications addressing dermatologic care in transgender patients were reviewed. According to the literature, there are several critical dermatologic considerations in transgender patients, including hair growth and removal, acne vulgaris, facial procedures to masculinize and feminize the face, scar removal, and sexually transmitted infections. CONCLUSION: As dermatologic surgeons have the privilege to improve the health care of transgender patients, they must understand the common and unique concerns of transgender individuals. Given the considerable spectrum of physical goals expressed by transmen and transwomen, individual patient preference must ultimately guide his/her/their dermatologic care.